KH. M. Mahsun Adnan dan Kontribusinya Bagi Perkembangan MI Al-Adnani Kayangan Diwek Jombang - Mukani (Institut Agama Islam Tribakti Kediri, 2021)
The madrasa role has long been recognized by community. Based on Law Number 20 of 2003 concerning National Education System, madrasa is a national education sub-system. This article is descriptive-analytic with a qualitative approach. The data was collected through interviews, documentation and observation. The data then analyzed by non-statistics, such as data reduction, data presentation and conclusion drawing. The study describes a brief biography of KH. M. Mahsun Adnan, he was born in Nglaban, he studied at Tebuireng, after that he studied at PGA. After graduating, he then continued his study at Undar and then dedicated himself to da'wah and education until his death. The second focus is the struggle of KH. M. Mahsun Adnan toward Al-Adnani Islamic Elementary School Jombang, starting from being a pioneer, becoming the head of a madrasa, teaching in it and fighting to make the madrasa run up. So far, Al-Adnani Islamic Elementary School Jombang shows its existence continuesly in bringing forword the community arround through education. [Peran madrasah telah lama diakui oleh masyarakat. Madrasah berdasarkan UU Nomor 20 Tahun 2003 tentang Sisdiknas adalah sebagai sub sistem pendidikan nasional. Artikel ini berjenis deskriptif-analitik dengan pendekatan kualitatif. Pengumpulan data melalui wawancara, dokumentasi dan observasi. Analisis data menggunakan non-statistik, yaitu reduksi data, penyajian data dan pengambilan kesimpulan. Pembahasan tulisan ini mendeskripsikan biografi singkat KH. M. Mahsun Adnan, mulai lahir di Dusun Nglaban, menimba ilmu ke Tebuireng, PGA dan kuliah di Undar lalu mengabdikan diri bagi dakwah dan dunia pendidikan hingga wafatnya. Fokus kedua adalah perjuangan KH. M. Mahsun Adnan kepada MI Al-Adnani Kayangan, mulai dari menjadi merintis, menjadi kepala madrasah, mengajar di dalamnya hingga berjuang agar madrasah tersebut tetap berkiprah. Hingga sekarang, MI Al-Adnani Kayangan tetap menunjukkan eksistensi dalam memajukan warga masyarakat sekitar melalui dunia pendidikan]